Coexistence of Primary GEJ Adenocarcinoma and Pedunculated Gastric Gastrointestinal Stromal Tumor. (11th June 2018) - Alkaaki, Aroub; Abdulhadi, Basma; Aljiffry, Murad; Nassif, Mohammed; Al-Maghrabi, Haneen; Maghrabi, Ashraf A.
Abstract : Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal tumors of the digestive system, although they account for only 0.1–3% of all gastrointestinal (GI) malignancies. They can arise anywhere along the GI tract with gastric predominance. Concurrent occurrence of GIST and gastroesophageal junction (GEJ) neoplasm is rare. We report a 55-year-old gentleman presenting with a polyp at the GEJ and a synchronous, large, and pedunculated gastric mass at the greater curvature. Those were treated with a wedge resection of the gastric pedunculated mass with negative margins along with transgastric submucosal resection of the GEJ polyp. Pathological examination confirmed synchronous invasive GEJ adenocarcinoma and a high-grade gastric GIST.